Evaluation of Government Initiatives for Endogenous Innovation The Government Innovation Competition in the Kingdom of Bahrain as a Model - Al-Noaimi, Hessa Abdulla (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to provide a better understanding of innovation in the context of the government sector by reviewing and evaluating the government innovation competition "Fikra", using the documentary analytical descriptive approach. The study reviews the most prominent outcomes of the government innovation competition in the Kingdom of Bahrain to provide an objective critique of the competition according to the nature of innovations presented and the aspects of development to be considered. The analysis included secondary sources consisting of government documents, official publications, and visual materials issued by the government of Bahrain during the period 2018-2021. In light of the results, the study recommendations emphasized the importance of investing in endogenous government innovation, as it is consistent with the nature of the government organizations and their work mechanisms. The study also developed a number of practical visions and perceptions for the attention of legislators and decision makers in the government of the Kingdom of Bahrain.